Management of indigenous vegetable genetic resources - Gangopadhyay, K K; Sharma, Vinod; Pragya, Pragya; Singh, Kuldeep (Indian Horticulture, 2020)
India being the primary centre of origin and secondary centre of diversity of many vegetable crops also possesses large variability in many important introduced vegetable crops. The success and pace of the development depends on the efficient use of plant genetic resources, viz. landraces, traditional varieties, wild, weedy and other related species constituting primary, secondary and tertiary gene pools. Wild relatives are incredible genetic resources carrying several desirable attributes like nutritional quality parameters, resistance to biotic and abiotic stresses that are generally lacking in the cultivated allies. ICAR-National Bureau of Plant Genetic Resources, New Delhi is the nodal agency for the management of national wealth of VGR, specially working for collections, characterization, identification and documentation of new germplasm.